Annual reports in medicinal chemistry - Doherty, Annette M.; ScienceDirect eBooks (New York : Academic Press, 2005)
Annual Reports in Medicinal Chemistry provides timely and critical reviews of important topics in medicinal chemistry together with an emphasis on emerging topics in the biological sciences, which are expected to provide the basis for entirely new future therapies. Sections I-IV are disease orientated and generally report on specific medicinal agents. Sections V and VI continue to emphasize important topics in medicinal chemistry, biology, and drug design. Section VII looks at Trends and Perspectives in the pharmaceuticals market. * Critical reviews of the previous year's literature in many topics of interest to medicinal chemists * Highlights major developments in medicinal chemistry * Includes a comprehensive set of cumulative indices to easily locate topics in all published volumes.
"Sponsored by the Division of Medicinal Chemistry of the American Chemical Society."
Print version record.
Elsevier
Keywords: Pharmaceutical chemistry; Clinical chemistry; Clinical chemistry; Pharmaceutical chemistry; Electronic books